TINJAUAN YURIDIS PEMANGGILAN NOTARIS DALAM PROSES PERADILAN - , anhar riadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research is purposed to find out the analysis public Notary summon in judicature prosses after Constitutional Court Decision Number 49/PUU-X/2012. Describe and explain the forms of legal protection public after Constitutional Court Decision Number 49/PUU-X/2012 and the new statute public Notary. This type of research is a blend of normative-empirical legal research which is based on secondary data (literature) and primary data (field). Based on the research objectives this research is a descriptive legal research legal research that would like to reveal things concerning the position role duties and authority National Notary Supervisory Assembly in Indonesia.The results of the research are: First, the legal process is not directly to a notary, namely through the Assembly Areas Supervisory. It is considered by the Constitutional Court is a form of discrimination before the law, second, the approval process for these Areas Supervisory Council is a form of negation to a legal process that is fast, efficient, and effective. Third, the process of calling in today's must see article 66A Act No. 2 by 2014 which set the grant of permission from the Tribunal of honor Notary which forms hitherto unclear. The form of protection it basically does not protect the âfullâ because in its development by a call to the Notary law enforcement today still to be served and when called upon the Notary can coordinate with the organization (Indonesian Institute of Notary) for the assistance given by organizational structure of Indonesian Institute of Notary authorized usually it is done by Advisory Agency of Indonesian Institute of Notary.